Hydroxyalkylation of p-Cresol to 2,2 `-methylenebis(4-methylphenol) using Sn/Si-MCM-41 catalysts - Garade, Ajit C.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Rode, Chandrashekhar V. (Chemistry Letters, 2010)
Sn/Si-MCM-41 has exhibited an excellent catalytic activity [70% product yield with 88% selectivity to 2,2'-methylenebis(4-methylphenol)] for the selective hydroxyalkylation of p-cresol. At equal level of Sn loading, Sn/Si-MCM-41 prepared by direct hydrothermal synthesis showed higher activity than Sn-impregnated Si-MCM-41 catalyst.

Hierarchical K/LTL zeolites: synthesis by alkali treatment, characterization and catalytic performance in knoevenagel condensation reaction - Tangale, Nilesh P.; Sonar, Shilpa K.; Niphadkar, Prashant S.; Joshi, Praphulla N. (Journal of Industrial and Engineering Chemistry, 2016)
The hierarchical K/LTL zeolites prepared by post-synthesis modification with aqueous 1.5 M KOH solution by varying alkali volume to K/LTL zeolite (10-70 ml/g) ratios, were examined in Knoevenagel condensation. The physico-chemical properties of the catalysts were thoroughly evaluated by PXRD, ICP, CO2-TPD, XPS, N-2 adsorption/desorption and Si-29 and Al-22 MAS-NMR. Among all the samples, hierarchical K/LTL prepared by treating K/LTL with 50 ml aqueous 1.5 M KOH solution per gram of K/LTL displayed about 1.5 fold higher catalytic activity as compared to parent K/LTL, presumably because of combined effect of enhanced basicity and molecular diffusion through pore channels. (C)2016 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.
Keywords: Basicity; Hierarchical zeolite; K/LTL; Knoevenagel condensation; Micro-mesoporous composite